Generator of User Interfaces for Mobile Applications from the Recognition of Patterns in Wireframes - Namuche, Valerie (2023)
The importance of mobile development has significantly grown as technology becomes more accessible, leading to increased interconnectivity in society. To keep pace with evolving trends, businesses and companies allocate development departments to create mobile applications that meet current and ever-changing needs. However, developers often encounter numerous challenges during the software development cycle. One common issue is the conversion of wireframes, which are designed to meet functional requirements and engage customers, into functional GUI code. This manual conversion process can be cumbersome, slow, and error-prone, consuming valuable time that could be spent on developing other functionalities. This paper aims to address this problem by introducing a website that offers an automated alternative to the wireframe-to-graphic user interface transformation process. Leveraging pattern recognition and machine learning techniques, the website streamlines and accelerates the conversion, eliminating the need for manual coding. Furthermore, the paper presents the results of a questionnaire administered to a group of software developers specializing in mobile development. The developers were shown a demo of the website, and their feedback and responses are analyzed and discussed.